An Analysis on the Components of Thesis Abstract at English Department - Anika Dwi Putri; Siska Siska; Melvina Melvina (English Teaching and Linguistics Journal (ETLiJ), 2023)
An abstract is one crucial element that contains an overview of a research report. However, the phenomenon found in several abstracts in students' theses is that the contents of the abstract have not been fulfilled according to the component of the abstract. The study aims to determine the elements of abstracts in the thesis of the 3rd graduate students of the UPGRISBA English Education Study Program. This type of research is descriptive qualitative. The data source for this research is 17 thesis. The Researchers used a checklist document as an instrument and content analysis to analyze the data obtained. The results showed that in the introduction part, only 6 fulfilled the component, and 11 did not. In the method section, only one is suitable, while the other 16 are not. In the results section, 16 fulfill the components of an abstract, and only one does not. In conclusion, eight is appropriate, and nine are not suitable with the features of an abstract. It can be concluded that the abstract component of the third graduate student's thesis is still incomplete. It is hoped that when writing an abstract, the writer must pay attention to the abstract features.